The management of acute appendicitis in liver transplant patients: How effective is the Alvarado score? - Ince, Volkan (North Clin Istanb, 2017)
OBJECTIVE: The incidence of acute appendicitis after liver transplantation (LT) is extremely low, reported to be 0.09% to 0.49%, but the efficacy of the Alvarado score in this patient group has not been studied. This study was an investigation of the clinical management of patients who developed acute appendicitis after LT and the usefulness of the Alvarado score in the diagnosis. METHODS: The study was performed using the data of 7 patients treated for acute appendicitis who were among 1990 patients who underwent LT between March 2002 and July 2017. The Alvarado score of the patients was calculated and reliability was analyzed. RESULTS: In this study, the incidence of acute appendicitis in LT patients was 0.35%. All of the patients were in the adult age group; 86% were male. The mean age was 46.4±10.7 years and the timeframe for the development of appendicitis after transplantation was a median of 12 months (range: 4-101 months). The median Alvarado score was 7 (range: 5-9). All of the patients had an Alvarado score above 5 and 71% had a score of 7 or more. CONCLUSION: Acute appendicitis is very rare in LT patients. As with non-transplant patients, Alvarado scoring can be safely performed in LT patients.